Between Compassion and Collapse: Alcohol Intake and Mental Health Challenges in Caregivers of Patients with Suicidal Behavior - Dhankar, Abhinav; Kumar, Kunal; Kumar, Abhinit; Nayar, Nikhil; Agrawal, Shlok; Jain, Soumya; Goyal, Ayushi (Journal of Neonatal Surgery, 2025)
Introduction: Suicidal behaviour poses significant public health concerns, not only for individuals but also for their caregivers, who often experience emotional distress. Alcohol use as a maladaptive coping strategy are underexplored in caregivers of individuals exhibiting suicidal behaviour . Method: This observational cross-sectional study was conducted from December 2023 to May 2024 at the Psychiatry Department of Sharda Hospital, Greater Noida. Eighty caregivers of patients with suicidal behaviour were enrolled using a convenience sampling method. Participants were assessed using a self-designed Case Record Form for demographic data, the and the Alcohol Use Disorder Identification Test (AUDIT) for alcohol use patterns. Statistical analysis was performed using SPSS 22.0, with associations analyse d using Chi-Square and ANOVA. Result: Among 80 caregivers, Alcohol use was identified in 28.8%, with a higher prevalence among male caregivers. Conclusion: Alcohol consumption are prevalent challenges among caregivers of suicidal patients, underscoring the need for targeted interventions to promote healthier coping mechanisms.